Indonesia’s 2023 Health Law Reframes Red Cross Blood Safety Accountability: Undang-Undang Kesehatan Indonesia Tahun 2023 Menata Ulang Akuntabilitas Keamanan Darah Palang Merah Indonesia - Dwi Nadhiro Salsabila Azizah; Lidya Shery Muis (Academia Open, 2026)
General Background:Blood services are essential to healthcare because they are directly connected to human safety, the right to life, and access to safe medical treatment. Specific Background:Mass blood donation contributes to national blood availability but may expose recipients to transmissible diseases, including HIV, when screening and safety standards are not consistently applied, placing legal responsibility on the Indonesian Red Cross as a blood-service provider. Knowledge Gap:Previous studies addressed blood screening, medical confidentiality, or institutional responsibility separately, without a specific and comprehensive examination of the development of the Indonesian Red Cross’s legal responsibility for blood safety in mass donation activities involving HIV risk. Aims:This normative legal study examines the development of legal regulation and Indonesian Red Cross responsibility through historical and statutory approaches, comparing Law Number 36 of 2009 and Law Number 17 of 2023 alongside related blood-service and human-rights regulations. Results:Law Number 17 of 2023 provides stronger provisions on safety, quality assurance, supervision, donor consent, and accountability, while retaining the Indonesian Red Cross as an authorized provider within a broader system of blood-service organizers. Its responsibility extends beyond humanitarian service to a legal obligation to protect the right to health and the right to life. Novelty:The study integrates normative legal analysis, public-health risk, mass blood donation practice, HIV-related screening, and legal consequences of negligence. Implications:Consistent implementation, rigorous screening, quality assurance, and sustained supervision are required to secure safe transfusion services and legal protection for donors and recipients. Highlights: The newer regulatory framework requires stricter quality assurance and supervision. PMI duties extend beyond humanitarian service to legally enforceable obligations protecting life. Consistent implementation and screening remainessential to safeguard transfusion recipients from HIV transmission Keywords: Indonesian Red Cross; blood safety; mass blood donation; legal responsibility; HIV transmission